Tindak Tutur Ekspresif pada Kolom Komentar YouTube KompasTV Berdasarkan Perspektif Cyberpragmatics - Apri Winda Winda; Fatmawati Fatmawati (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The background of this research is expressive speech act in social media to describe and elaborate the function of expressive speech act based on cyberpragmatics perspective. This study uses a qualitative approach to the content analysis method. The source of data in this study is all language activities contained on the comment page uploaded on September 25, 2023 with a total of 5,832 speeches. The data in this study are all expressive speech acts contained in the comments column totaling 366 utterances. Data collection techniques used are listen, documentation, and record techniques. The research was conducted through YouTube because it makes it easier for netizens to express their speech through the comments column. Based on the analysis, 9 functions of expressive speech acts were found to praise, criticize, congratulate, welcome, accuse, complain, berate, insult and support. The function of speech acts that often arise is the function of praise because it is a form of admiration for someone by the speaker. Speech act the function criticizing serves to provide direction or constructive criticism, function congratulating the form of congratulations on an achievement, function welcoming is expressed when receiving something with a feeling of pleasure, function accusing arises because there is a feeling of dislike for the interlocutor, function complaining expresses a complaint against something, function berating is expressed berating interlocutor, function insulting lowers the degree of speech partner, and function supporting providing support to speech partner. In this study did not find the function of speech acts to thank, sympathize, yell, apologize, forgive, and express condolences.